2016
DOI: 10.1002/psc.2850
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced antimicrobial activity of a peptide derived from human lysozyme by arylation of its tryptophan residues

Abstract: Antimicrobial peptides are valuable agents to fight antibiotic resistance. These amphipatic species display positively charged and hydrophobic amino acids. Here, we enhance the local hydrophobicity of a model peptide derived from human lysozyme (107RKWVWWRNR115) by arylation of its tryptophan (Trp) residues, which renders a positive effect on Staphylococcus aureus and Staphylococcus epidermidis growth inhibition. This site-selective modification was accessed by solid-phase peptide synthesis using the non-prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 20 publications
(24 reference statements)
0
10
0
Order By: Relevance
“…The minimum inhibitory concentration (MIC) of the hydrogel toward S. aureus was determined to be around 3 mg/mL (24 μM of IKFQFHFD peptide), which is comparable or superior to most of the reported antimicrobial peptides (Figure S10). , Subsequently, scanning electronic microscopy (SEM)-based bacterial morphology study and live/dead bacterial staining assay were carried out to investigate the specific mechanism behind the pH-switchable antimicrobial activity of self-assembled IKFQFHFD hydrogel. As shown in Figure b, S. aureus cells incubated with the hydrogel in pH 7.4 showed clear edges and smooth bodies.…”
Section: Resultsmentioning
confidence: 99%
“…The minimum inhibitory concentration (MIC) of the hydrogel toward S. aureus was determined to be around 3 mg/mL (24 μM of IKFQFHFD peptide), which is comparable or superior to most of the reported antimicrobial peptides (Figure S10). , Subsequently, scanning electronic microscopy (SEM)-based bacterial morphology study and live/dead bacterial staining assay were carried out to investigate the specific mechanism behind the pH-switchable antimicrobial activity of self-assembled IKFQFHFD hydrogel. As shown in Figure b, S. aureus cells incubated with the hydrogel in pH 7.4 showed clear edges and smooth bodies.…”
Section: Resultsmentioning
confidence: 99%
“…These cationic amino acids confer aqueous solubility to the peptide and also allow for electrostatic interaction with the negatively charged bacterial cell wall, 5,6 while the hydrophobic character of the peptide facilitates interaction with the lipid bilayer membrane of bacteria. 7,8 One of the proposed mechanisms of action for cationic AMPs is inhibition of the cell wall biosynthesis via binding to lipid II, the precursor of cell wall synthesis in Gram-positive microorganisms. For example, plectasin binds to lipid II and prevents its incorporation into the peptidoglycan chain.…”
Section: ■ Introductionmentioning
confidence: 99%
“…As such, they have a hydrophilic character as a result of the presence of a relatively high percentage of Arg and Lys residues. These cationic amino acids confer aqueous solubility to the peptide and also allow for electrostatic interaction with the negatively charged bacterial cell wall, , while the hydrophobic character of the peptide facilitates interaction with the lipid bilayer membrane of bacteria. , …”
Section: Introductionmentioning
confidence: 99%
“…5 A large number of studies have shown that the biological activity of AMPs is closely related to the positive charge. 6 At the same time, the a-helix secondary structure also plays an important role in maintaining the bioactivity of AMPs. The amphiphilicity of AMPs is one of the important factors affecting the antibacterial activity.…”
Section: Introductionmentioning
confidence: 99%